Thermal signatures of voluntary deception in ecological conditions - Panasiti, Maria Serena (Sci Rep, 2016)
Deception is a pervasive phenomenon that greatly influences dyadic, groupal and societal interactions. Behavioural, physiological and neural signatures of this phenomenon have imporant implications for theoretical and applied research, but, because it is difficult for a laboratory to replicate the natural context in which deception occurs, contemporary research is still struggling to find such signatures. In this study, we tracked the facial temperature of participants who decided whether or not to deceive another person, in situations where their reputation was at risk or not. We used a high-sensitivity infrared device to track temperature changes to check for unique patterns of autonomic reactivity. Using a region-of-interest based approach we found that prior to any response there was a minimal increase in periorbital temperature (which indexes sympathetic activation, together with reduced cheek temperature) for the self-gain lies in the reputation-risk condition. Crucially, we found a rise in nose temperature (which indexes parasympathetic activation) for self-gain lies in the reputation-risk condition, not only during response preparation but also after the choice was made. This finding suggests that the entire deception process may be tracked by the nose region. Furthermore, this nasal temperature modulation was negatively correlated with machiavellian traits, indicating that sympathetic/parasympathetic regulation is less important for manipulative individuals who may care less about the consequences of lie-related moral violations. Our results highlight a unique pattern of autonomic reactivity for spontaneous deception in ecological contexts.